PENGUATAN RESPONSIVE CAREGIVING BAGI CAREGIVER - Formen, Ali; Sugiana, Sugiana; Rohmah, Naili; Kiswanto, Kiswanto; Tarigan, Novelia Danesya; Muthianabila, Lisa; Saputra, Nikola (DEVOSI, 2025)
The primary and fundamental education for a child begins within the family. Early childhood requires optimal caregiving from those around them, particularly their parents. However, in today's reality, many young parents are engaged in work, leading to child caregiving responsibilities being entrusted to caregivers, daycare centers, or other family members. According to data, 84.33% of Indonesian children are raised by both biological parents, while 2.51% are raised solely by their father, 8.43% solely by their mother, and 4.76% by other family members. In the Mangunsari area, caregivers are not only responsible for childcare but are also burdened with household chores, which divides their attention and reduces focus on the child. Therefore, introducing the responsive caregiving module serves as a solution to enhance the quality of childcare for children under the age of three.This community service initiative aims to improve caregiver competencies through the introduction of the responsive caregiving module, enhance their understanding of child development milestones, and develop their skills in providing educational games and creating appropriate play materials for child development. The implementation method consists of five stages: preparation, training and education, practical experience, mentoring, and evaluation with feedback. The results indicate that the responsive caregiving module effectively enhances caregivers' competencies in providing responsive care. Based on interviews and observations, 92% of participants showed improved understanding, while 89% demonstrated increased skills in responding to children's needs and desires. Therefore, this initiative contributes to improving the quality of childcare in the Mangunsari area of Semarang City.